TOURISM DESTINATION MANAGEMENT ORGANISATIONS IN THE SOUTH TRANSDANUBIAN REGION - Pálfi, Andrea; Aubert, Antal (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
The present article studies and introduces the characteristics and activities of the South Transdanubian tourism destination management (TDM) organisations through the results of an online questionnaire survey. The aim of this research is to reveal the tourism management activities of the South Transdanubian tourism region and to introduce its characteristics regarding either the basic TDM characteristics (number of members, settlements within the area of operation, operation form) or the characteristics of operative activities. Thus, based on a former research we studied and analysed the nine TDM organisations of the selected area in a national comparison as well. Though the South Transdanubian tourism region is not one of the most visited tourism regions of Hungary the results showed that the tourism management activity is quite intensive. The co-operation among the TDM organisations, actors of tourism supply, the service providers and the operators of attractions is promising, whilst the statewide problems and the local operational difficulties can also be observed here as well.